India : 2019 Article IV Consultation-Press Release; Staff Report; Staff Statement and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation with India discusses that India has been among the world's fastest-growing economies in recent years, lifting millions out of poverty. However, growth slowed to a six-year low in the first half of 2019, with both consumption and investment decelerating owing to weak, especially rural, income growth, stresses in the nonbank financial sector, and corporate and environmental regulatory uncertainty. On the external sector, following a rise in vulnerabilities in 2018, stability has returned, anchored by high foreign reserve buffers and a modest current account deficit. With its strong mandate, the new government has an opportunity to reinvigorate the reform agenda aimed at boosting inclusive and sustainable growth. In the near term, given the cyclical weakness of the economy, monetary policy should maintain an easing bias at least until the projected recovery takes hold. Fiscal stimulus should be avoided given fiscal space at risk and revenue losses from the recent corporate income tax rate cut should be offset.